PENGEMBANGAN PEMBELAJARAN TAQRAR FIQIH BERBASIS TEORI CLASSICAL CONDITIONING DALAM MENINGKATKAN HASIL BELAJAR SANTRI ASRAMA D PESANTREN NGALAH PASURUAN - Lailatul Fitriah; Muhammada; Ahmad Ma’ruf; Ahmad Yusuf (IAIN Ambon, 2024)
The field research aims to describe the development of Ivan Pavlov's classical conditioning theory by providing rewards to create an increase in students' learning outcomes in learning taqrar fiqh. This research focuses on a qualitative research approach with a descriptive approach that uses data collection techniques through observation, interviews and documentation. This research case study was carried out in dormitory D of the Ngalah Pasuruan Islamic Boarding School which focused on 2 taqrar fiqh classes. The results of this research show that classical conditioning theory influences the improvement of students' learning outcomes in learning taqrar fiqh. This is marked by a change in each individual student who has enthusiasm and interest in learning, thus creating exemplary students. The implication of this research is that classical conditioning theory can be applied to other materials to produce increased learning outcomes in all materials.